Exploration of pressure ulcer and related skin problems across the spectrum of health care settings in Ontario using administrative data - Kevin Woo; Kim Sears; Joan Almost; Rosemary Wilson; Marlo Whitehead; Elizabeth G. VanDenKerkhof (2015)
Abstract This is a prospective cohort study using population‐level administrative data to describe the scope of pressure ulcers in terms of its prevalence, incidence risk, associating factors and the extent to which best practices were applied across a spectrum of health care settings. The data for this study includes the information of Ontario residents who were admitted to acute care, home care, long term care or continuing care and whose health care data is contained in the resident assessment instrument‐minimum data set ( RAI‐MDS ) and the health outcomes for better information and care ( HOBIC ) database from 2010 to 2013. The analysis included 203 035 unique patients. The overall prevalence of pressure ulcers was approximately 13% and highest in the complex continuing care setting. Over 25% of pressure ulcers in long‐term care developed one week after discharge from acute care hospitalisation. Individuals with cardiovascular disease, dementia, bed mobility problems, bowel incontinence, end‐stage diseases, daily pain, weight loss and shortness of breath were more likely to develop pressure ulcers. While there were a number of evidence‐based interventions implemented to treat pressure ulcers, only half of the patients received nutritional interventions.